HUBUNGAN PENGETAHUAN TENTANG MENSTRUASI DENGAN PERILAKU PERSONAL HYGIENE PADA REMAJA PUTRI DI DESA SUTAWINANGUN KABUPATEN CIREBON - Sofiyati Sofiyati (Consilium Sanitatis: Journal of Health Science and Policy, 2023)
Objective: The research objective was to determine the relationship between knowledge about menstruation and personal hygiene behavior during menstruation in young women in Sutawinangun Village, Kedawung District, Cirebon Regency. Methods: This research is an analytic survey with a cross-sectional time approach. The population is 62 respondents, using total sampling with a total sample of 62 young women. The instrument was used to measure the knowledge and behavior of respondents using a questionnaire. Results: Description of young women's knowledge about menstruation in Sutawinangun Village, Kedawung District, Kab. Cirebon data were obtained from 62 respondents; 33 of them had enough knowledge (53.2%), while only 8 respondents (12.9%) had a good understanding, and 21 respondents (33.9%) had less knowledge. As for the behavior of young women regarding personal hygiene, the results showed that 41 people had positive personal hygiene behavior during menstruation (66.1%). In contrast, 21 respondents (33.9%) had negative personal hygiene behavior during menstruation. Based on the calculation results of Kendall tau, P-value = 0.000 < α = 0.05 (the P-value is more minor than α = 0.05). This means a significant relationship exists between young women's knowledge of personal hygiene behavior during menstruation. Conclusion: There is a Relationship between Knowledge about Menstruation and Personal Hygiene Behavior During Menstruation in Young Women in Sutawinangun Village, Kedawung District, Cirebon Regency.